Financial Distress Prediction Models in Property Sector Companies Listed in Indonesia Stock Exchange - Meita Tri Herlina; Werner Ria Murhadi (IPTEK Journal of Proceedings Series, 2020)
Along with the unstable national and global economic conditions, investors and consumers defend themselves to invest in the property sector. Companies go public in obtaining capital markets as a means to obtain sources of funds. Investors and creditors will see the financial condition required before the company will increase financial distress (financial distress) or not before investing their capital. Therefore, analysis and prediction of a company's financial problems is very important. This study uses the Financial Distress model by using discriminant analysis. The independent variables used are financial ratios which are divided into 4 categories (1) Liquidity Ratios, (2) Solvency Ratios, (3) Activity Ratios, (4) Profitability Ratios. This research uses quantitative with the Multivariate Discriminant Analysis (MDA) model. The sample data used in this study includes property, real estate, and construction sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. This study produces a financial distress model Z-score = -3,569 + 6,910DTA -1.107DTE + 7,515ROE + 3,573OPM with a cut-off value of -3,521. When the z-score of the company -3,521, the company is included in the non-financial pressure group.